1994
DOI: 10.4319/lo.1994.39.7.1653
|View full text |Cite
|
Sign up to set email alerts
|

A field study of metal toxicity and accumulation by benthic invertebrates; implications for the acid‐volatile sulfide (AVS) model

Abstract: The toxicity and accumulation of Cd from sediment by benthic invertebrates was measured along a Cd gradient created in nature. The efficacy of acid-volatile sulfide (AVS) concentrations in improving the prediction of biological effects in nature is also evaluated for the first time. The Cd concentration of sediments from a shield lake in Quebec was adjusted to obtain Cd : AVS ratios of from 0.05 to 10. The sediments were then subjected to in situ colonization by invertebrates over a 1 -yr period. Cd concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
159
1
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(172 citation statements)
references
References 33 publications
10
159
1
2
Order By: Relevance
“…The species-specific aspects of bioaccumulation could result from difference in feeding mode (filter feeding vs deposit feeding), exposure routes (dissolved vs food or benthic vs pelagic food web) and duration of exposure, as well as internal processes such as storage, detoxification and loss (Jackim et al 1977, Roesijadi & Robinson 1994, Wallace & Lopez 1996, Reinfelder et al 1997. Experimental studies have shown, for example, differences in metal uptake between suspension feeding and deposit feeding bivalves exposed in the same metal-ennched system (Crecelius et al 1982, Bryan 1985 or between benthos that feed from the water column versus benthos that feed on the sediments (Hare et al 1994, Warren et al 1998. It is proposed that some organisms can internally maintain or regulate approximately constant tissue levels of selected elements (most commonly Zn), regardless of external metal concentrations (Rainbow et al 1990 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The species-specific aspects of bioaccumulation could result from difference in feeding mode (filter feeding vs deposit feeding), exposure routes (dissolved vs food or benthic vs pelagic food web) and duration of exposure, as well as internal processes such as storage, detoxification and loss (Jackim et al 1977, Roesijadi & Robinson 1994, Wallace & Lopez 1996, Reinfelder et al 1997. Experimental studies have shown, for example, differences in metal uptake between suspension feeding and deposit feeding bivalves exposed in the same metal-ennched system (Crecelius et al 1982, Bryan 1985 or between benthos that feed from the water column versus benthos that feed on the sediments (Hare et al 1994, Warren et al 1998. It is proposed that some organisms can internally maintain or regulate approximately constant tissue levels of selected elements (most commonly Zn), regardless of external metal concentrations (Rainbow et al 1990 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…is restricted to this zone, whereas the other taxa penetrate some distance into anoxic sediment. Because the concentrations of dissolved and particulate trace metals tend to change with the redox conditions (Hare et al 1994), the exposure of animals to these contaminants is likely tn differ depending on the depth to which they burrow.…”
mentioning
confidence: 99%
“…), it has the potential to play a major role in bioturbation. We also wanted to determine the depth to which this insect and other sympatric taxa burrow to compare their potential relative exposures to sedimentary contaminants, the distributions of which tend to be strongly vertically stratified (Hare et al 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the EqP approach only accounts for a few metals and is limited by a variety of restrictions (14)(15)(16). Further, SQVs derived from the AVS/SEM model do not always show an improved ability to predict absence of sediment toxicity compared to SQVs based on dry-weight concentrations (17)(18)(19).…”
Section: Metal and Metalloid Sediment Quality Valuesmentioning
confidence: 99%